"I Kept Coming for the Love": Enhancing the Retention of Urban African Americans in Diabetes Education. (May 2014) - Raffel, Katie E.; Goddu, Anna P.; Peek, Monica E.
Purpose: The purpose of the study was to investigate how retention strategies employed by the Diabetes Empowerment Program (DEP) contributed to retention. Methods: An experienced moderator conducted in-depth interviews (n = 7) and 4 focus groups (n = 29) with former DEP participants. Interviews were recorded, transcribed, and coded using iteratively modified coding guidelines. Results were analyzed using Atlas.ti 4.2 software. Results: Participants were African American and predominantly female, low income, and with more than 1 diabetes complication. Key retention themes included: (1) educator characteristics and interpersonal skills ("The warmth of the staff . . . kept me coming back for more."), (2) accessible information ("I didn't know anything about diabetes [before]. I was just given the medicine."), (3) social support ("I realized I wasn't the only one who has diabetes."), (4) the use of narrative ("It's enlightening to talk about [my diabetes]."), and (5) the African American helping tradition ("I went not just for myself but for my husband."). Conclusions: While many interventions focus on costly logistics and incentives to retain at-risk participants, study findings suggest that utilizing culturally tailored curricula and emphasizing interpersonal skills and social support may be more effective strategies to retain low-income African Americans in diabetes education programs.